Relapse Versus Reinfection of Recurrent Tuberculosis Patients in a National Tuberculosis Specialized Hospital in Beijing, China - Zong, Zhaojing; Huo, Fengmin; Shi, Jin; Jing, Wei; Ma, Yifeng; Liang, Qian; Jiang, Guanglu; Dai, Guangming; Huang, Hairong; Pang, Yu (Frontiers in Microbiology, 2018)
Tuberculosis (TB) recurrence can result from either relapse of an original infection or exogenous reinfection with a new strain of Mycobacterium tuberculosis (MTB). The aim of this study was to assess the roles of relapse and reinfection among recurrent TB cases characterized by a high prevalence rate of drug-resistant TB within a hospital setting. After 58 paired recurrent TB cases were genotyped to distinguish relapse from reinfection, 37 (63.8%) were demonstrated to be relapse cases, while the remaining 21 were classified as reinfection cases. Statistical analysis revealed that male gender was a risk factor for TB reinfection. Meanwhile, compared with patients without comorbidities, TB patients with diabetes mellitus were more likely to be classified as relapse than reinfection cases. Of MTB isolates obtained from the 37 relapse cases, 11 exhibited conversion from sensitivity to resistance to at least one antibiotic, with the most frequent emergence of drug resistance observed to levofloxacin. For reinfection cases, reemergence of rifampicin-resistant isolates harboring double gene mutations, of codon 531 of rpoB and codon 306 of embB, were observed. In conclusion, our data demonstrate that relapse is a major mechanism leading to TB recurrence in Beijing Chest Hospital, a national hospital specialized in TB treatment. Moreover, relapse is more common in diabetic patients, while male patients are at higher risk for reinfection. The extremely high rate of multidrug-resistant tuberculosis (MDR-TB) among reinfection cases reflects more successful transmission of MDR-TB strains versus non-resistant strains overall.